Mother–Infant Skin-to-Skin Contact: Short‐ and Long-Term Effects for Mothers and Their Children Born Full-Term - Bigelow, Ann E.; Power, Michelle (Frontiers in Psychology, 2020)
This brief report reviews findings from a longitudinal study of skin-to-skin contact (SSC) with mothers and full-term infants and a follow-up study of these dyads when the children were nine years. Findings infer the positive influence of SSC on mother-child interaction in infancy and into children’s middle childhood. Mothers and infants in SSC and control groups were seen when infants were one week, one month, two months, and three months. SSC group mothers reported fewer depressive symptoms in infants’ early weeks and had greater reduction in salivary cortisol, a physiological stress indicator, in infants’ first month. SSC group mothers who initially chose to breastfeed continued to breastfeed their infants throughout the three months, whereas breastfeeding mothers in the control group declined over the visits. When engaged in the Still Face Task with their mothers, SSC group infants showed the still face effect with their affect at one month, a month before control group infants did so. At three months, SSC group infants were social bidding to their mothers during the still face phase. When the children were nine years, the mother-child dyads engaged in conversations about the children’s remembered emotional events. Mother-child dyads who had been in the SSC group showed more engagement and reciprocity in the conversations than mother-child dyads who had been in the control group. Oxytocin, induced by SSC, is inferred to be an underlying factor that helped the mother-infant relationship have a positive trajectory with long-term benefits.